Dampak Pengelolaan Sumberdaya Manusia Terhadap Semangat Kerja Karyawan PT Bukit Jaya Abadi Surabaya - Sri Susilowati; Ilya Farida (Universitas 17 Agustus 1945 Surabaya, 2016)
This research aims to know and analyze the impact human resource management insimultan and partial that influence toward employees morale of PT Bukit Jaya AbadiSurabayya. And find out the most dominan variable that influenced.The population of thisresearch is the permanent employes which has about 95 personal there.method samplingused stastitied random sampling technical with 75 sample.Variable of this research includethe variable of human resource management (X), consisting variable of selection (X),Development (X2), compensation (X3), maintance (X), with significant (α) 5%. Analysismodel, which is used is Multiple Regression Analysis that F-tes and t-test.Based on theresearch results shows the F-test that human resource management (X), including ofSelection (X1), Development (X2), Compensation (X903)4, Maintance (X) variable in simultanthat influenced toward employees morale (Y). It is proven F-count 6,148 > F-table 2,5 .while F-test, that influence the employees morale (Y) it is prove t-count -3.258 > t- tabel 1.6669with significant 0,000.Based on the research results shows the t-test that Selection (X41) and Maintance (X)variable in partial that influenced toward employees morale (Y). It is proven, that Selection(X) t-count 3,258 > t-table-1,666 with significant 0,002, wile It is proven, that Maintance(X14) variable t-count -2,786 > t-table-1,6669 with significant 0,007. Selection (X) is themost dominan variable that influenced toward employees morale (Y). Which contribute thewhole variable on the variation employees morale is 26,01%, that is R2=0,2601. While therest of a big 73,99% that influenced variable other that don’t exist in this research.Keywords: Human, Resource, Management, Employees, Morale